Aluminum exposure promotes histopathological and pro-oxidant damage to the prostate and gonads of male and female adult gerbils - da Silva Lima, Danilo; da Silva Gomes, Liana; de Sousa Figueredo, Esther; de Godoi, Murion Monteiro; Silva, Edvaldo Mendes; da Silva Neri, Hiasmin Franciely; Taboga, Sebastião Roberto [UNESP]; Biancardi, Manoel Francisco; Ghedini, Paulo César; dos Santos, Fernanda Cristina Alcantara (Elsevier, 2020)
Since the industrial revolution, all living beings have become susceptible to numerous sources of aluminum (Al) exposure. In addition to causing proven toxicity in many organs and systems, Al can also have estrogenic activity when absorbed by the body. The reproductive organs are commonly affected by environmental pollutants with estrogenic activity, but little is known about the effects of Al on the prostate and gonads. Therefore, the aim of this study was to evaluate the effects of subchronic Al exposure on the prostate and gonads of male and female adult gerbils. After 30 days of oral exposure to aluminum chloride (10 mg/kg/day), the animals were euthanized and the organs processed for cytochemical, ultrastructural, and biochemical assays. Ventral male prostates exposed to Al became hyperplastic and showed signs of cell aging. In addition, the male prostate showed decreased catalase (CAT) and superoxide dismutase (SOD) activity. The female prostate was structurally more affected than the ventral male prostate, since it presented hyperplasia and punctual foci of inflammation and prostatic intraepithelial neoplasia. However, CAT and SOD activities did not change in this gland. In the testis, Al promoted immature germ cell detachment and degeneration, as well as reduced CAT activity. In the ovaries, Al caused reduction in folliculogenesis and decreased SOD activity. Together, these results indicate that Al is toxic to the prostate and gonads of adult gerbils and that continuous exposure to this metal can impair the fertility of individuals of both sexes.
Keywords: Environmental pollutants; Female prostate; Metalloestrogens; Oxidative stress; Ultrastructure; Ventral male prostate